2017
DOI: 10.1099/ijsem.0.002303
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus petauri sp. nov., isolated from an abscess of a sugar glider

Abstract: A strain of lactic acid bacteria, designated 159469T, isolated from a facial abscess in a sugar glider, was characterized genetically and phenotypically. Cells of the strain were Gram-stain-positive, coccoid and catalase-negative. Morphological, physiological and phylogenetic data indicated that the isolate belongs to the genus Lactococcus. Strain 159469T was closely related to Lactococcus garvieae ATCC 43921T, showing 95.86 and 98.08 % sequence similarity in 16S rRNA gene and rpoB gene sequences, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 22 publications
(22 reference statements)
1
24
0
Order By: Relevance
“… L. garvieae was first described as Streptococcus garvieae in 1983 ( 1 ) and subsequently separated into subgroups A and B ( 2 ). Genomic analysis reassigned L. garvieae subgroup A strains to the recently described species L. petauri ( 3 ). Consequently, both species can be considered the etiological agents of lactococcosis in fish ( 4 , 5 ) and emerging opportunistic zoonotic pathogens ( 6 8 ).…”
Section: Announcementmentioning
confidence: 98%
“… L. garvieae was first described as Streptococcus garvieae in 1983 ( 1 ) and subsequently separated into subgroups A and B ( 2 ). Genomic analysis reassigned L. garvieae subgroup A strains to the recently described species L. petauri ( 3 ). Consequently, both species can be considered the etiological agents of lactococcosis in fish ( 4 , 5 ) and emerging opportunistic zoonotic pathogens ( 6 8 ).…”
Section: Announcementmentioning
confidence: 98%
“…As a new feed additive, Lactococcus can optimize the structure of intestinal flora and promote the growth of mice. Lactococcus petauri is facultative anaerobic, non-motile, non-spore forming, and Gram-positive [13]. Yet there are few probiotic functional pieces of evidence of Lactococcus petauri published as mostly probiotics have strains specific properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that Lactococcus lactis was present in the gastrointestinal tract of the infant on the first day of the life (Park et al, 2005). Lactococcus petauri has the closest relationship with L. garvieae and is a facultative anaerobic, non-motile, non-spore forming, Grampositive cocci (Goodman et al, 2017). To date, L. petauri has been obtained in a facial abscess of a sugar glider alone, and no functional evidence was published.…”
Section: Introductionmentioning
confidence: 99%